Analisis Kualitas Pelayanan P.T. Kereta Api Indonesia terhadap Tingkat Kepuasan Pengguna Jasa pada Stasiun Cepu - Budiarto, Balla Wahyu; Priyanto, Sigit; Muthohar, Imam (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
PT. KAI is a State-Owned Enterprise that provides rail transportation services. The purpose of this study is to provide recommendations for improvement of the main priority level of service user satisfaction to service providers PT. KAI towards improving services at Cepu Station which refers to the Minimum Service Standards (SPM) at stations contained in PM 63 of 2019 concerning Minimum Service Standards for Transportation of People by Train. This study uses a quantitative descriptive research type. The target of this research is to know the value of CSI, IPA and the calculation of the PGCV Index which is useful for assisting the IPA method in attribute improvement. The results of this study obtained a CSI value of 74%, namely with the predicate of being satisfied, the results of the IPA which became a priority to improve the quality of quadrant I and quadrant III and with the PGCV method the priority of improving service quality attributes that must be immediately repaired was in quadrant I there were 2 attributes namely station cleanliness, toilet cleanliness and comfort.Keywords: service quality, satisfaction level, Customer Satisfaction Index, Importance Performance Analysis, Potential Gain in Customer Value